SIMPLE ADDITIVE WEIGHTING UNTUK PENGEMBANGAN WEB EMPLOYEE PERFORMANCE APPRAISAL (WEMPA) PADA RUMAH SAKIT KRAKATAU MEDIKA CILEGON - Tb Ai Munandar (LPPM Unbaja, 2022)
Krakatau Medika Hospital is a privately operated hospital in Cilegon. Employee performance appraisal is highly significant at each agency, where organizational goals can be reached by each employee, one of which is the achievement of work targets. Currently, Krakatau Medika Cilegon Hospital requires an employee performance appraisal system that can aid the assessment process by employing the proper approach but does not affect the assessment criteria or the assessment methodology that has been set. The employee performance appraisal method employed in the study and in determining the performance value is the Simple Additive Weighting (SAW) approach with four (four) criteria, including the Attendance Criteria, Performance Criteria, Attitude Criteria, and Infrastructure Criteria. This web-based system was created utilizing Unified Modeling Language (UML) modeling, the PHP programming language, and Sublime Text program management with MySQL and XAMPP databases. The findings of system testing using Black Box were performed by two (two) IT personnel to demonstrate that the system can work by user requirements. Calculation tests utilizing the system and instructions get the same results.